Different levels of cardiometabolic indicators in multiple vs. singleton children - Maria João Fonseca; Ana Cristina Santos; Henrique Barros (BMC, 2019)
Abstract Background We aimed to compare cardiometabolic indicators in singletons and multiples at age 7 and explore the birthweight mediation effect. Methods We studied 5431 singletons and 103 sets of multiples from Generation XXI birth cohort. Anthropometric measurements, body composition, and fasting blood samples were obtained. Age- and sex-specific z-scores were calculated (additionally height-specific for blood pressure). Adjusted regression coefficients and respective 95% confidence intervals [β (95%CI)] were computed using path analysis. Results Multiples had lower weight [− 0.419 (− 0.616;-0.223)], height [− 0.404 (− 0.594;-0.213)], BMI [− 0.470 (− 0.705;-0.234)], fat mass index [− 0.359 (− 0.565;-0.152)], waist circumference [− 0.342 (− 0.537;-0.147)], and waist-to-height ratio [− 0.165 (− 0.326;-0.003)] z-scores. These results were explained by the indirect effect via birthweight, which was also negative and significant for all the aforementioned cardiometabolic indicators, while no direct effect was present. There were also significant indirect effects regarding fat-free mass index, glucose, insulin, and blood pressure, though the total effects were not significant, due to the balance between direct and indirect effects. The only significant direct effect was regarding diastolic blood pressure [− 0.165 (− 0.302;-0.028)]. Conclusions At age 7, multiples presented better cardiometabolic indicators explained by lower weight at birth, except for the lower blood pressure which was independent of an effect via birthweight.